Acidic isoforms of Erwinase form part of the product: Correlation with clinical experience. (March 2020) - Gervais, David
Abstract: Erwinia chrysanthemi l -asparaginase (ErA) has been used for the treatment of acute lymphoblastic leukaemia (ALL) for decades, and its safety and efficacy have been well demonstrated. ErA drug substance and drug product contain a small proportion of acidic isoforms, with a known mechanism of formation, which have been shown to be minor conformational variants retaining enzymatic activity and function. Specifications for these acidic isoforms were set with an extremely limited data set, and with further manufacturing experience, it can now be demonstrated that they were set too tightly. Here, we consider the ability of the manufacturing process to meet the current acidic isoforms specifications, as well as clinical outcomes from drug product containing a higher proportion of isoforms. Compared with the historical clinical experience with the drug, there appeared to be no difference in the rate of adverse event reporting (e.g., hypersensitivity or other events) when drug product with relatively higher acidic isoforms was administered. ErA acidic isoforms comprise part of the ErA product and appear to have no clinical relevance, so a realignment of process capability and specification may be warranted. Biopharmaceutical developers should exercise caution when setting specifications with limited data, to avoid process capability pitfalls later.